Case report: Clinical, imaging, and genetic characteristics of type B niemann pick disease combined with segawa syndrome diagnosed via dual gene sequencing - Wu, Fang; Su, Dongying; Wang, Weisi; Song, Xia; Fan, Shufeng; Su, Jinzhan; Ma, Linying; Xu, Jianxia; Rao, Qinpan (Frontiers in Genetics, 2024)
Niemann Pick disease B (NPB) often presents with hepatosplenomegaly and lung pathological changes, but it usually does not present with central nervous system symptoms. This report presents the unique case of a 21-year-old woman with a 10-year history of hard skin and hepatosplenomegaly. Genetic sequencing revealed NPB and also suggested Segawa syndrome. Although symptomatic supportive treatments were administered in an attempt to improve muscle tone and treat the skin sclerosis, their efficacy was not satisfactory, and the patient refused further treatment. This case provides several noteworthy findings. First, although NPB and Segawa syndrome are rare, both are autosomal recessive inherited diseases that share common clinical symptoms and imaging manifestations. Second, when NPB and Segawa syndrome are highly suspected, screening for tyrosine hydroxylase (TH) and sphingomyelin phosphodiesterase-1 (SMPD1) gene mutations is critical to determine an accurate diagnosis. Finally, early diagnosis and comprehensive therapies are crucial for improving the prognosis of patients with NPB and Segawa syndrome.